Knowledge, attitude, and practices regarding sterilization protocol among dental students at Kanpur, Uttar Pradesh: A percentage-based study - Vishal Mehrotra; Shazia Aslam; Kriti Garg; Rahul Srivastava; Pallavi Sinha; Jyoti Kiran (Wolters Kluwer Medknow Publications, 2022)
Context: Infection control and prevention is an major part of patient care. Concerns about the possible spread of blood-borne diseases and the impact of emerging highly contagious respiratory and other illnesses require practitioners to establish, evaluate, continually update, and monitor their infection prevention and control strategies and protocols. Aims: The aim of this study was to assess the level of knowledge, attitude, and practice among dental students about sterilization protocol. Settings and Design: A questionnaire-based survey was conducted. Subjects and Methods: A total of 220 dental students comprising undergraduates and postgraduates participated in the survey where they were provided to fill a modified pretested, self-administered questionnaire consisting of 10 questions. Statistical Analysis Used: The data were collected, compiled, arranged systematically, and analyzed in terms of percentage and frequencies. Participant's response was calculated and expressed as percentages and frequency. Results: The clinical dental students showed a positive level of awareness, knowledge, and practice toward the sterilization protocols and infection control in their day-to-day practice. Conclusions: Dental care professionals are at an increased risk of cross-infection as well as its transmission while treating the patients. This study is based on to assess the level of knowledge, attitude, and practice among dental students about sterilization protocol.